Triple-blinded randomized clinical trial comparing efficacy and tooth sensitivity of in-office and at-home bleaching techniques - Sandrina Henn DONASSOLLO; Tiago Aurélio DONASSOLLO; Sumaia COSER; Sabrina WILDE; Juliana Lays Stolfo UEHARA; Luiz Alexandre CHISINI; Marcos Britto CORREA; Maximiliano Sérgio CENCI; Flávio Fernando DEMARCO (University of São Paulo, 2021)
Abstract Objective Our study aims to compare the efficacy and tooth sensitivity following in-office (35% hydrogen peroxide) or at-home (10% carbamide peroxide) bleaching treatments both preceded by 2% potassium nitrate (2%KF) desensitizing gel. Methodology 130 volunteers were randomly allocated to a) in-office bleaching and a placebo at-home protocol; or b) in-office placebo and at-home bleaching treatment. 2% KF was applied for 10 min before both treatments. Objective color evaluation was performed (spectrophotometer CIEL*a*b* system and CIEDE2000) to calculate the color change (ΔE00). Subjective evaluation was performed using the VITA classical shade guide followed by shade variation (ΔSGU) at the beginning and end of bleaching treatment and 2 weeks post-bleaching. Tooth sensitivity was daily recorded using a Likert scale varying from 1 (no sensitivity) to 5 (severe sensitivity). Analysis was carried out using non-parametric tests. Results Regarding the color change, at-home bleaching resulted in significant color improvement compared to in-office treatment for the parameters Δb* (p=0.003) and Δa* (p=0.014). Two weeks post-bleaching, the at-home treatment resulted in significant color improvement compared to in-office treatment for the parameters Δb* (p=0.037) and ΔE00 (p=0.033). No differences were observed in either ΔSGU parameters. Concerning sensitivity, patients treated with in-office bleaching reported more tooth sensitivity than the at-home group only on the first day after bleaching started, without significant differences in the other periods evaluated (p>0.05). Conclusions At-home and in-office bleaching, preceded by a desensitizing agent, were effective for vital teeth bleaching and 10% carbamide peroxide produced a higher whitening effect than 35% hydrogen peroxide in the short time evaluation. Tooth sensitivity rates were similar for the two techniques tested.